Function and Role of Histamine H1 Receptor in the Mammalian Heart - Joachim Neumann; Britt Hofmann; Uwe Kirchhefer; Stefan Dhein; Ulrich Gergs (MDPI AG, 2023)
Histamine can change the force of cardiac contraction and alter the beating rate in mammals, including humans. However, striking species and regional differences have been observed. Depending on the species and the cardiac region (atrium versus ventricle) studied, the contractile, chronotropic, dromotropic, and bathmotropic effects of histamine vary. Histamine is present and is produced in the mammalian heart. Thus, histamine may exert autocrine or paracrine effects in the mammalian heart. Histamine uses at least four heptahelical receptors: H1, H2, H3 and H4. Depending on the species and region studied, cardiomyocytes express only histamine H1 or only histamine H2 receptors or both. These receptors are not necessarily functional concerning contractility. We have considerable knowledge of the cardiac expression and function of histamine H2 receptors. In contrast, we have a poor understanding of the cardiac role of the histamine H1 receptor. Therefore, we address the structure, signal transduction, and expressional regulation of the histamine H1 receptor with an eye on its cardiac role. We point out signal transduction and the role of the histamine H1 receptor in various animal species. This review aims to identify gaps in our knowledge of cardiac histamine H1 receptors. We highlight where the published research shows disagreements and requires a new approach. Moreover, we show that diseases alter the expression and functional effects of histamine H1 receptors in the heart. We found that antidepressive drugs and neuroleptic drugs might act as antagonists of cardiac histamine H1 receptors, and believe that histamine H1 receptors in the heart might be attractive targets for drug therapy. The authors believe that a better understanding of the role of histamine H1 receptors in the human heart might be clinically relevant for improving drug therapy.